Biodegradable Mg-Ca/Mg-Cu bilayer membranes with enhanced mechanical, osteogenesis and antibacterial performances for GBR applications - Yanbo Shan; Bo Qiao; Sihui Ouyang; Chengao Du; Lisheng Zhao; Gang Wang; Jianting Ye; Yingjie Xiong; Yu Wei; Jiangfeng Song; Jia She; Jiang Peng; et al. (Journal of Magnesium and Alloys)
Magnesium (Mg) alloys with biodegradability and excellent mechanical properties are in high demand for applications in guided bone regeneration (GBR). However, the clinical application of Mg alloys is hindered by infection risks and limited osteogenesis. Herein, a structure-functional integrated Mg-Ca/Mg-Cu bilayer membrane was rolled at 150 °C through various single-pass reductions by using online heating rolling. The Mg-Cu layer was specifically engineered to exhibit antibacterial properties tailored for gingival tissue, while the Mg-Ca layer was designed to support bone regeneration within the defect cavity. The bilayer membrane demonstrated a flexural yield strength of 421.0 MPa and a modulus of 58.6 GPa, indicating exceptional deformation resistance. Furthermore, it maintained notable structural stability by retaining 86.4% of its volume after 21 days in Hanks' solution. In vitro results revealed that the bilayer membrane exhibited favorable biocompatibility and promoted osteogenesis via the synergetic effect of released Mg2+ and Ca2+ ions. The rapid release of Cu2+ ions and the creation of an alkaline environment further improved antibacterial properties, potentially preventing postoperative infections. Additionally, in an in vivo rat calvarial defect model, the membrane demonstrated its capability to stimulate new bone formation. In summary, the Mg-Ca/Mg-Cu bilayer membrane exhibited outstanding mechanical stability, favorable corrosion rates, extraordinary osteogenic and antibacterial activity simultaneously. Consequently, it holds promise as a robust barrier membrane in GBR applications.